INTEGRATION OF QUR'ANIC VALUES IN ISLAMIC RELIGIOUS EDUCATION IN THE MODERN ERA - Muhammad Abri Harahap (Program Pascasarjana UIN Sumatera Utara, 2026)
This article discusses the importance of integrating Qur'anic values into Islamic Religious Education (PAI) in the modern era. Religious education is not only about knowledge transmission but also value transformation. In the context of globalization and the challenges of the digital age, Qur'anic values such as monotheism, morality, justice, and knowledge become the foundation for shaping students' holistic character. This study uses a qualitative library research method with a thematic approach to Qur’anic verses and relates them to PAI learning practices. The results show that Qur'anic values can be integrated into the curriculum, methods, and evaluation of PAI to form faithful, knowledgeable, and noble-minded individuals. The article concludes that Qur’anic-based PAI can be a solution to the moral and spiritual crises among students today.